Volume 5: Ocean Engineering; CFD and VIV 2012
DOI: 10.1115/omae2012-83316
|View full text |Cite
|
Sign up to set email alerts
|

On the Dynamic Response of Flexible Risers Caused by Internal Slug Flow

Abstract: Slug flow through flexible risers is a frequent phenomenon which occurs during production of a mixture of oil and gas. The dynamic nature of the slug pattern induces time varying forces, which leads to structural vibrations of the riser. These vibrations can produce large deflections and stresses, which can leave it to fail by fatigue, excessive bending or local buckling. In this work the influence from slug flow on the structural dynamic response of a lazy wave flexible riser is analyzed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Seyed and Patel (1992) deduced an analytical model for calculating the pressure and internal slug flow induced forces on flexible risers. Ortega et al (2012) reported a computational method to analyze the interaction between an internal slug flow and the dynamic response of flexible risers. Extending previous work, Ortega et al (2013) studied the interaction between an internal slug flow plus an external regular wave and the dynamic response of a flexible riser.…”
Section: Introductionmentioning
confidence: 99%
“…Seyed and Patel (1992) deduced an analytical model for calculating the pressure and internal slug flow induced forces on flexible risers. Ortega et al (2012) reported a computational method to analyze the interaction between an internal slug flow and the dynamic response of flexible risers. Extending previous work, Ortega et al (2013) studied the interaction between an internal slug flow plus an external regular wave and the dynamic response of a flexible riser.…”
Section: Introductionmentioning
confidence: 99%
“…This way of analysis performs numerical solution for both pipe flow and structural response, where relevant forces and geometry changes are communicated between the physical phenomena in order to include the influence of the flow dynamics in the structural response and vise-versa. Ortega et al (2012) studied the influence of slug flow in the dynamic response of a lazy wave riser using a feedback connection between a structural dynamic software and a multiphase flow software by means of high level architecture. Ortega et al (2017) used an improved structural model in order to predict the influence of waves and slugs in the movement of a catenary riser.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the VIV response can be stationary in some parts (due to current) while in other parts it may be intermittent (due to relative oscillatory flow). In addition, internal slug flow may also cause riser vibrations [9], which will interact with the VIV response. To capture all these effects, a non-linear time domain analysis is required.…”
Section: Introductionmentioning
confidence: 99%